Malaysia My Second Home (MM2H): Retirees' demographic profile and spending dynamics. (June 2017) - Wong, Brian Kee Mun; Musa, Ghazali
Abstract: While most of the second home retirement tourism studies are qualitative in nature, knowledge on retirees' demographic profile and their spending dynamics is limited. We sampled Malaysia My Second Home (MM2H) participants at multiple data collection points, and received 504 usable completed questionnaires for analysis. The majority of the participants (56.3%) are aged between 60 and 69 years, mainly from Japan, the UK, and Australia. Their favourite residential locations are Klang Valley, Penang, Langkawi, Sabah, and Sarawak. Most of them stay about 10–12 months yearly in Malaysia, and spend an average of RM 6030 a month. Based on the recorded 29, 390 second home participants, we calculate the potential direct spending contribution from MM2H participants to the Malaysian economy as RM 1.68 billion a year. We propose some marketing and managerial recommendations. Highlights: We purposively sampled 504 MM2H retirees at multiple locations. They are mainly from Japan, the UK, and Australia, aged between 60 and 69 years old. Top residential locations are Klang Valley, Penang, Langkawi, Sabah, and Sarawak. The majority of them stay for about 10–12 months a year in Malaysia. They spend RM6, 030/month, contributing about RM1.68 billion/year to Malaysian economy.